Sharing the Luck: An Introduction to KOINON IV with Recourse to Hermes - Molinari, Nicholas J. (KOINON: The International Journal of Classical Numismatic Studies, 2021)
Hermes might be the most dynamic of all the Greek deities—a marginal figure in the truest sense, he is both a trickster and thief, yet also a source for ingenuity and insight. He is associated with peace, eroticism, relationships, hermeneutics (of course), and even comedy, to name just a few of his many attributes. At home in both Olympus and Hades, or among men or women, he is as pervasive in Greek culture as he is mysterious and difficult to pin down.